The Effect Of Yoga Exercise On Anxiety In Menopausal Women At Babakan Sari Sub-District, Bandung City - Sri Hayati; Tukimin (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Introduction: Menopausal women experience various physical and psychological problems. One of the psychological problems that often arises is anxiety. Anxiety occurs because a decrease in estrogen causes a decrease in serotonin, a chemical that carries messages between nerve cells in the central nervous system, gut, blood, and humans. The impact of menopausal women's anxiety is a decrease in quality of life. One intervention that is easy and safe to do is yoga. Yoga exercise has movements that are relaxing so that it can be used to reduce anxiety. This study aims to determine the effectiveness of yoga exercises to reduce anxiety in menopausal women. Method: The research design used quasi-experimental with pretest and posttest. The population in this study were women aged > 45 years. Samples were taken using purposive sampling. The inclusion criteria were women>45 years who had experienced menopause. The exclusion criteria were menopausal women taking anti-anxiety drugs. The instrument is in the form of a Zung self-rating anxiety scale questionnaire sheet which consists of normal, mild anxiety, moderate anxiety, and severe anxiety. Results: It shows that in the pretest, the majority of respondents had mild anxiety 34 people (68%); in the posttest, the majority of respondents became normal, namely 32 people (64%). The results of the t-test showed p-value = 0.00, < a = 0.05, so yoga interventions are proven to reduce anxiety in menopausal women. Discussion: Yoga exercises are effective in reducing anxiety because yoga exercises provide relaxation for postmenopausal women, with interventions given every 3 times a week for 3 weeks, increasing the effectiveness of yoga in reducing anxiety. Every movement in yoga has a relaxing effect, which if done continuously can reduce body tension and anxiety. Intervening 9 times for three consecutive weeks has been proven to reduce anxiety, initially mild to most normal. So yoga is proven to reduce anxiety in menopausal women. Every movement in yoga has a relaxing effect, which if done continuously can reduce body tension and anxiety. So yoga is proven to reduce depression in menopausal women. Conclusion: Yoga exercises are effective in reducing anxiety in menopausal women. Suggestions for other researchers are yoga interventions on the anxiety of chronic disease patients.